The mechanical properties of concrete in water environment: A review - Wang, Juan; Sun, Ke; Hu, Yu; Guan, Qiaoyan; Li, Qingbin (Frontiers in Materials, 2022)
The service performance of concrete structures in a water environment differs from that in a normal environment. An accurate evaluation of the mechanical properties and service status of wet concrete is related to the reliable design and safe operation of concrete structures, e.g., hydraulics, marine engineering, bridges, and tunnels. To promote the application of new and high-performance concrete to complex water environments and grasp the future development trend, the research progress on the service performance of concrete in water environments was reviewed worldwide. Starting from the internal moisture content of concrete, the existing research is combed, the influence of moisture content, water pressure, and loading rate on the static and dynamic characteristics of concrete in a water environment is summarized, and the influence mechanism is analyzed. The literature review demonstrate that the static compressive strength of wet concrete is lower than that of dry concrete; however, the elastic modulus improves. With an increase in the strain rate, the compressive strength of wet and dry concretes improves, and the rate sensitivity of the wet concrete is greater than that of the normal concrete. Pore structure characteristics mainly affect the static strength of the wet concrete. The improvement in the dynamic strength of the wet concrete is caused by the combined effect of the concrete rate sensitivity, “Stefan” effect, and water pressure.